Correction: Using an RNA aptamer probe for super-resolution imaging of native EGFR. Issue 2 (8th January 2019) - Yan, Qiuyan; Cai, Mingjun; Zhou, Lulu; Xu, Haijiao; Shi, Yan; Sun, Jiayin; Jiang, Junguang; Gao, Jing; Wang, Hongda
Abstract : Correction for 'Using an RNA aptamer probe for super-resolution imaging of native EGFR' by Qiuyan Yan et al., Nanoscale Adv., 2019, DOI: ; 10.1039/c8na00143j .